Ways of spending free time by teachers of physical education in Tarnów - Anita Ziemba (University of Applied Sciences in Tarnow, Poland, 2019)
Aim of the study: The aim of the work was to conduct research in the field of interests and their impact on spending free time by physical education teachers teaching at schools in Tarnów. Material and methods: The research was carried out in 2018 among 30 teachers in the 30-50 age group, teaching physical education in primary schools, junior high schools and upper secondary schools in Tarnow, taking part in thematic workshops. The research was carried out by means of a diagnostic survey, and a survey technique was used to obtain the necessary information and data. Results: The surveyed PE teachers most often spend their free time actively outside home, and most preferably with the family and friends. Sport was the most popular choice among respondents, regardless of gender. Clear gender differences were noted in the areas of spending free time, interests and hobbies. Conclusions: The vast majority of PE teachers surveyed spend their free time actively, mainly interested in sport. Women are more interested in health and beauty, and men in film and music, motorization and DIY.